Entrepreneurial Self-efficacy and Extreme Decision-making: The Unexpected Influence of Entrepreneurial Personality - Chatpunyakul, Chatchai (Animo Repository, 2024)
The two main goals of this paper are to (a) examine how entrepreneurial self-efficacy (ESE) affects decision- making among nascent entrepreneurs and (b) examine the moderating role of entrepreneurial personality. A 2x2 between- subjects online randomized experiment was carried out. A sample of 48 Bangkok-based business school students who functioned as the study’s nascent entrepreneurs’ representatives was used to collect data for two sessions. Multiple linear regression was used to assess the research hypotheses. The findings show that extreme decision-making and nascent entrepreneurs’ ESE are positively correlated; an increase in ESE causes an increase in extreme decision-making. The effect of ESE on decision-making, however, was not found to be positively moderated by entrepreneurial personality. The results of this study have important academic and practical implications for both academic institutions and nascent entrepreneurs. When encouraging ESE and entrepreneurial decision-making, it is important to consider the too-much- of-a-good-thing (TMGT) effect.